The Role of Audit committees in Earnings quality An Empirical Study on Banks listed on the Damascus Securities Exchange - عاصي أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The aim of the research is to study the relationship between the elements of auditing and the quality of accounts for companies. Especially the factor in the stock market, and for that, as well as the data on the variable dependent on the quality of accounting through the report and reports. The financial statements of the financial banks, the Securities and Exchange Commission, the Securities Commission, and 12 banks during the period from 2010 to 2017, and the data was studied through the Eviews10 program. The study reached a set of results, the most important of which are: There is no statistically significant effect between the variables of the audit committee represented by: the number of audit committee meetings with the external auditor, the number of annual committee meetings, the number of independent members, the availability of financial and accounting experience in the audit committee and the variable of earnings quality, and the direction of the relationship between these variables is reversed except Only the independence variable, the direction of the relationship with the earnings quality variable, is positive, but not statistically significant.